Pencegahan Bullying di Sekolah Melalui Program “Welcome Day” - Budi Sarasati; Dian Kusumawati; Iin Wdiastuti (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
This community service activity is motivated by the condition of problems in the environment of Junior High School (SMP) of Global Insani Islamic School (GIIS); it has been found that one of the problems that is deemed necessary to watch out is in terms of interaction with fellow Junior High School students. Based on the observation of the school, in this case is the teacher, the intercommunications of Junior High School students are considered "braver". In the sense of sometimes "forgetting" the risks or dangers they face. If we learn further, then the risk behavior among Junior High School students can be caused by the adaptation process in the face of puberty and also in the face of changes in the style of intercourse in adolescence. Risky behaviors that become the most widespread problem are the behaviors associated with bullying and the behaviors of intercommunication with understanding of sexuality.